Author Correction: Misestimation of heritability and prediction accuracy of male-pattern baldness - Chloe X. Yap (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of the author Julia Sidorenko, which was incorrectly given as Julia Sirodenko. This has now been corrected in both the PDF and HTML versions of the Article. Further, the sixth sentence of the second paragraph of the Correspondence and the legend to Fig. 1 incorrectly omitted citation of work by Heilmann-Helmbach, S. et al. This has now been corrected in both the PDF and HTML versions of the Article.